Mode of action of the hemin-controlled inhibitor of protein synthesis: studies with factors from rabbit reticulocytes. - de Haro, C (1978)
Previously [de Haro, C., Datta, A & Ochoa, S. (1978) Proc. Natl. Acad. Sci. USA 75, 243--247] it was shown with initiation factors from Artemia salina embryos that the activity of the initiator methionyl-tRNA binding factor eIF-2 is stimulated by another factor (ESP, for eIF-2 stimulating protein) present, like eIF-2, in ribosomal salt washes. Incubation of eIF-2 with translational inhibitor from rabit reticulocytes, in the presence of ATP, abolished the ESP effect. At physiological concentrations eIF-2 was virtually inactive without ESP. These observations indicated that the translational inhibitor acts by converting eIF-2 to a form that is not stimulated by ESP. The same observations have now been made with eIF-2 and ESP from rabbit reticulocytes but, in this case, the dependence of eIF-2 activity on ESP is much more pronounced than with the A. salina factors. eIF-2 from reticulocytes interacts with ESP from A. salina and conversely.